Fabrication and properties of ternary Al-Mg-Zn alloy filled with polypropylene: Progress report - Teoh, Ai Ling; Mohd Ichwan, Nasution, Prof. Madya Ir. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.